The Effects of Core Strength Training on Lower Back Pain in Workers - Metta Christiana; Andy Kridasusila; Albert Albert; Rusmalia Dewi (Universitas Pahlawan Tuanku Tambusai, 2026)
Low Back Pain (LBP) is one of the most common health problems experienced by workers across various sectors and across all ages. LBP has the highest prevalence among musculoskeletal conditions worldwide and is also a leading cause of disability worldwide, requiring rehabilitation for most sufferers. Work environments and types involving prolonged sitting or sedentary work, heavy lifting, or non-ergonomic postures significantly contribute to the prevalence of LBP. LBP is often a major cause of absenteeism, decreased productivity, and a reduced quality of life for workers. Core Strength Training (CST) programs are one approach that is gaining increasing attention. CST is considered an effective intervention for strengthening core muscles, increasing stability, and reducing strain on the low back. The authors aimed to evaluate the effects of CST on LBP in workers. By understanding the specific benefits of CST, it is hoped that more effective recommendations for preventing and managing LBP can be developed, thereby improving worker health and productivity and avoiding disability in old age. This study aimed to evaluate the effectiveness of CST in reducing the intensity of LBP in workers. This study will employ a mixed methods design with a pre-experimental approach, employing a one-group pretest-posttest design for quantitative analysis and in-depth interviews for qualitative analysis. The population comprised residents of Tlogosari Kulon and Tlogosari Wetan who were still actively working and experiencing low back pain. Data collection was conducted over six weeks, with two weekly training sessions. The research instrument was the research team itself, while the instruments used were a Numerical Rating Scale (NRS) and an observation sheet using the PQRST mnemonic method: Provokes (Causes) and Palliatives (Relieves), Quality (Quality), Radiates (Radiates), Severity (Severity), and Time (Time). Quantitative analysis used the Kolmogorov-Smirnov test for data normality. Qualitative analysis employed thematic analysis. Data triangulation was performed by comparing interview results with quantitative data.